2021
DOI: 10.1097/njh.0000000000000754
|View full text |Cite
|
Sign up to set email alerts
|

Religious Involvement, Depressive Symptoms, and Burden in Caregivers of Terminally Ill Patients

Abstract: Caring for terminally ill patients can be emotionally burdensome. Previous research has demonstrated that caregiving is associated with anxiety and depression. Research on caregivers of terminally ill patients is limited by retrospective studies with small samples. This study aimed to (1) describe religiosity, religious coping, and depressive symptoms in caregivers of persons with amyotrophic lateral sclerosis or advanced cancer; (2) examine the relationship between religiosity and depressive symptoms in careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…In contrast, others showed instead greater skepticism and sometimes anger and signs of spiritual crisis, consequent to losing their loved one (such as Giacomo, for example). These different possible approaches to the end-oflife theme are both supported by other studies in the literature, with research that has confirmed the protective value of spirituality for people suffering from severe terminal illnesses and for their families [66][67][68][69], who manage to maintain higher levels of hope and less despair. In contrast, other studies have reported that the illness of a loved one can contribute significantly to spiritual crises and a perceived loss of meaning in existence [70].…”
Section: Qualitative Discussionsupporting
confidence: 57%
“…In contrast, others showed instead greater skepticism and sometimes anger and signs of spiritual crisis, consequent to losing their loved one (such as Giacomo, for example). These different possible approaches to the end-oflife theme are both supported by other studies in the literature, with research that has confirmed the protective value of spirituality for people suffering from severe terminal illnesses and for their families [66][67][68][69], who manage to maintain higher levels of hope and less despair. In contrast, other studies have reported that the illness of a loved one can contribute significantly to spiritual crises and a perceived loss of meaning in existence [70].…”
Section: Qualitative Discussionsupporting
confidence: 57%
“…The main religions practised in Sri Lanka; Buddhism, Christianity, Islam and Hinduism highlight the importance of love and care, particularly for those who are sick. These values are inculcated very early in life and may determine the way caregivers handle the pressure and strain associated with the long-term caregiving of their loved ones [ 24 , 25 ]. Furthermore, patients with malignancies, especially those who are incurable, receive the sympathy of people and it is not uncommon for caregivers of cancer patients to show more resilience.…”
Section: Discussionmentioning
confidence: 99%
“…43 Regarding the impact of caring responsibilities, more caregiving hours and less relaxation 44 and greater carer burden 43 also related to worse mental health. More active coping 45 and less negative religious coping 46 were associated with better health, and being female was associated with worse health. 44 Formal care support also appeared to matter.…”
Section: Comparison With Previous and Recent Literaturementioning
confidence: 95%